Big Swiss : a novel - Beagin, Jen (New York : Scribner, 2023)
"Greta lives with her friend Sabine in an ancient Dutch farmhouse in Hudson, New York. The house, built in 1737, is unrenovated, uninsulated, and full of bees. Greta spends her days transcribing therapy sessions for a sex coach who calls himself Om. She becomes infatuated with his newest client, a repressed married woman she affectionately refers to as Big Swiss, since she's tall, stoic, and originally from Switzerland. Greta is fascinated by Big Swiss's refreshing attitude toward trauma. They both have dark histories, but Big Swiss chooses to remain unattached to her suffering while Greta continues to be tortured by her past. One day, Greta recognizes Big Swiss's voice at the dog park. In a panic, she introduces herself with a fake name and they quickly become enmeshed. Although Big Swiss is unaware of Greta's true identity, Greta has never been more herself with anyone. Her attraction to Big Swiss overrides her guilt, and she'll do anything to sustain the relationship..."--Provided by publisher.
Keywords: Female friendship -- Fiction; Deception; Dogs; Female friendship; Infatuation; Sex therapy; Swiss Americans; Transcription; Novels